Drinking Behavior and Mental Illness Among Evacuees in Fukushima Following the Great East Japan Earthquake: The Fukushima Health Management Survey. (20th February 2016) - Ueda, Yuka; Yabe, Hirooki; Maeda, Masaharu; Ohira, Tetsuya; Fujii, Senta; Niwa, Shin‐ichi; Ohtsuru, Akira; Mashiko, Hirobumi; Harigane, Mayumi; Yasumura, Seiji; ,
Abstract : Background: Recent evidence from alcohol and trauma studies suggests that disasters are associated with increases in the consumption of alcohol. The Great East Japan Earthquake and the associated nuclear disaster have continued to affect the mental health of evacuees from Fukushima. This study aimed to extend these findings by examining the relationship between drinking behaviors and the risk of mental illness after the compound disaster. Methods: We conducted the Mental Health and Lifestyle Survey with 56, 543 evacuees. Kessler's K6 was used to assess the risk of mental illness, and logistic regression models were applied to analyze how drinking behavior patterns influence the risk of serious mental illness after adjustment for confounding variables. Results: Logistic regression analysis evidenced that beginning heavy and light drinkers had the highest and a higher risk of serious mental illness, respectively. Individuals who were nondrinkers pre‐ and postdisaster had the lowest proportional risk of mental illness. Abstainers also had some risk to their mental health after the compound disaster. Conclusions: The results of this study highlight that beginning drinkers have a high risk of serious mental illness. Thus, mental health professionals should pay attention to the drinking behaviors of evacuees, which might predict increased risk of serious mental illness and consequently indicate a need for psychological intervention. Abstract : This study examined relationships between drinking behaviors and the risk of mental illness among evacuees after a compound disaster. Figure summarizes how participants' drinking behavior pattern influenced the risk of serious mental illness. The beginning heavy and light drinkers had the highest and a higher risk of serious mental illness, respectively, even after adjusting for socioeconomic and disaster‐related factors. It should be noted that drinking behavior patterns are key to assessing the risk of serious mental illness among evacuees.